2021
DOI: 10.1039/d0dt03093g
|View full text |Cite
|
Sign up to set email alerts
|

Evolution from a single relaxation process to two-step relaxation processes of Dy2 single-molecule magnets via the modulations of the terminal solvent ligands

Abstract: To explore the influences of the magnetic interactions on the relaxation dynamics of single-molecule magnets (SMMs) and to understand the relationship between single-ion relaxation and the relaxation of a molecular...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…Despite the presence of two crystallographically independent dysprosium sites for 1 , the fitting of the Cole–Cole plots with the generalized Debye model yields α values in the range of 0.311–0.407 (Table S3, ESI†), indicating a moderate distribution of relaxation times. 52 From these data, the relaxation time, τ , could be extracted in order to analyse the relaxation dynamics. The ln( τ ) vs. T plot (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the presence of two crystallographically independent dysprosium sites for 1 , the fitting of the Cole–Cole plots with the generalized Debye model yields α values in the range of 0.311–0.407 (Table S3, ESI†), indicating a moderate distribution of relaxation times. 52 From these data, the relaxation time, τ , could be extracted in order to analyse the relaxation dynamics. The ln( τ ) vs. T plot (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…23 Furthermore, the lattice solvent molecules can also sometimes change the symmetry of the crystals and lead to a different number of the crystallographic unique Ln III centers, which can lead to the appearance of multiple relaxation processes. 24 Fourth, modification of the Ln-SMMs through solvents can sometimes occur in the solid state through a desolvation/ solvation process and, even more interestingly, in a reversible single-crystal-to-single-crystal manner. Up to now, several Ln III complexes with these solvent-switchable properties have been reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, Liu et al also reported four very similar Cu 3 Tb 2 compounds where the noncoordinated solvents [methanol (MeOH), ethanol (EtOH), propanol (PrOH), and water (H 2 O)] can have a continuous modification of their energy barriers . Furthermore, the lattice solvent molecules can also sometimes change the symmetry of the crystals and lead to a different number of the crystallographic unique Ln III centers, which can lead to the appearance of multiple relaxation processes …”
Section: Introductionmentioning
confidence: 99%
“…7 Among several ligand systems employed for the development of Dy-SMMs, Schiff base ligands possessing rich N/O donor sites have been extensively used in the synthesis of such SMMs mainly due to their ease of synthesis and possible modulation of electronic and steric properties by suitable choice of carbonyl and amine components. 8 In our previous work, we successfully isolated some lanthanide complexes with a symmetrical dinucleating Schiff base ligand derived from 4-chloro-2,6-diformylphenol and N , N -dimethyldipropylenetriamine in which Dy analogues displayed SMM properties. 9 Remarkably, the metal assisted in situ macrocyclization of the acyclic heptadentate N 6 O donor Schiff base ligand was observed in the presence of co-ligands (acetylacetone or its derivative) by defragmentation of some parts of the ligands.…”
Section: Introductionmentioning
confidence: 99%